Tradisi Musik Vokal Singiran Sebagai Media Pembelajaran Budi Pekerti pada Anak Santri di Jawa - Jarmani, Jarmani (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
Singiran is one of the art of vocal music in the form of poetry sung through a song, whether in Arabic or Javanese, which is very well known in traditional Javanese Islam. This study uses a qualitative approach by applying research concepts that are in accordance with the conditions in the field, in this case qualitative research which becomes an instrument or research tool is the research itself. Data collection techniques using document studies and field studies, namely interviews and observation. From the results of data collection it turns out that singir has been neglected by the community, and it turns out that singir has a very meaningful function for its supporters, namely the use of a number of singers in the learning of children's character. With the view of the function of singir art, educators, especially art, should be even more creative in innovation about education through art media. Keywords: singiran, learning media, student.